Aberrant expression of SPAG6 and NM23 predicts poor prognosis of human osteosarcoma - Bao, Zhengqi; Zhu, Ruizhi; Fan, Huagang; Ye, Yuchen; Li, Tian; Chai, Damin (Frontiers in Genetics, 2022)
Objective: To investigate on expressions and clinical significances of sperm- associated antigen 6 and NM23 proteins in human osteosarcoma. Methods: The specimens of conventional osteosarcoma with follow-up from 42 Chinese patients were analyzed in this study and 12 cases of osteochondroma were considered as controls. The expression of SPAG6 and NM23 was inspected by using immunohistochemical staining, qRT-PCR and Western blot methods. Results: The positive expression rate of SPAG6 protein (71.43%) in 42 cases of osteosarcoma tissue was significantly higher than that 33.33% in 12 cases of osteochondroma tissue (P<0.05). While the positive rate of NM23 protein (35.71%) in osteosarcoma tissue was lower than that 58.33% in osteochondroma tissue (P<0.05). The mRNA and protein level of SPAG6 was significantly higher than the adjacent normal tissues, while the expression of NM23 was lower in osteosarcoma tissues than that in controls (P<0.05 for all). There were a positive relationship between the expression of SPAG6 and pathological grade, metastasis and Enneking stage (P<0.05 for all). The overall survival rate of the osteosarcoma patients with SPAG6 positive expression was significantly lower than that of osteosarcoma patients with SPAG6 negative expression. The relationship between the expression of NM23 and pathological grade, metastasis and Enneking stage was negative (P<0.05 for all). The overall survival rate of the osteosarcoma patients with NM23 positive expression was higher than those patients with NM23 negative expression (P<0.05). Conclusion: Aberrant-expression of SPAG6 and NM23 are positively and negatively, respectively, related to pathological grade, metastasis and Enneking stage and prognosis of osteosarcoma patients. It suggested that SPAG6 and NM23 should be considered as a possible marker for the prognosis.